Revealing the Profile of Foster Parents, Biological Parents, Foster Children and the Triadic Relationship amongst them - Farmakopoulou, Ignatia; Baltsioti, Vasiliki (Technium Social Sciences Journal, 2024)
This research paper explores the foster care framework in Greece, with a particular focus on the triadic relationship among foster carers, biological parents, and foster children. It refers to the current 30 hours compulsory training program of foster parents, emphasizing the necessity of a further specialized comprehensive training, on the ground that well prepared foster carers can better face the complexities of fostering. There is also an imperative need for ongoing support for foster parents, which will be provided in the context of social workers’ supervision to meet the behavioral and emotional challenges presented by foster children. The study investigates the potential hindrances faced during the child’s placement within the foster home and the vital role social workers play in addressing these difficulties. It delves into the backgrounds of biological parents, foster carers, and foster children, examining the psychological issues and trauma they may confront. The paper highlights the paths of creating an emotional bond, trusting relationships, amongst the child and his/her foster parents and contact issues between foster and biological parents, asserting that these elements are crucial for the child’s well-being and his/her integration into the foster family. Moreover, it recognizes the need for policy makers and practitioner’s collaboration and interdisciplinary approaches within the foster care system. The study concludes that well-structured support, the empowerment of children through resilience building, and a stable legal framework are foundational to successful application of the institution of fostering. It encourages future research in the form of longitudinal studies, the evaluation of training models, and cross-national comparisons that include Greek foster care organizations to ameliorate the effectiveness of foster care system. The research incorporates theoretical and research studies articles as well as selected books in the field to underline the importance of evidence-based practices in advancing the application of the institution of foster care as well as the experiences of both foster care children, biological and foster parents.